Azelastine‐Fluticasone Intranasal Combination Therapy in Otorhinolaryngology: Clinical Evidence, Current Practice Patterns and Future Perspectives - Giorgio Ciprandi; Ignazio La Mantia; Attilio Varricchio (Clinical Otolaryngology, 2026)
ABSTRACT Background Allergic rhinitis (AR) represents a significant burden in Ear Nose Throat (ENT) practice and markedly affects quality‐of‐life and work productivity of AR patients. The fixed combination of intranasal azelastine and fluticasone propionate (AzeFlu) has emerged as a valuable therapeutic option for moderate‐to‐severe AR. Recent updates to international guidelines and real‐world evidence warrant a comprehensive review of its role in ENT practice, with particular attention to both seasonal and perennial AR. Methods This narrative review synthesises evidence from the ARIA‐EAACI 2024–2025 guidelines, systematic reviews and network meta‐analyses of randomised controlled trials, pharmacovigilance data, and results from an Italian multidisciplinary inter‐societal Delphi Consensus. We evaluated efficacy, safety, patient acceptability and implementation considerations specific to otorhinolaryngology practice. Results Network meta‐analyses demonstrate that AzeFlu provides superior symptom control compared to monotherapy for both nasal and ocular symptoms in seasonal and perennial AR, with a rapid onset of action (15–30 min). The combination shows particular efficacy in patients with moderate‐to‐severe symptoms inadequately controlled by monotherapy. Safety profiles are comparable to those of monotherapy, with no significant effects on growth or the HPA axis in children. Real‐world data indicate high treatment satisfaction and adherence. The Italian Delphi Consensus achieved > 80% agreement on key management principles, particularly emphasising control of Type 2 inflammation and the role of combination therapy in treatment algorithms. Evidence for perennial AR remains more limited, and future primary research specifically targeting perennial rhinitis populations is warranted. Conclusions Azelastine‐fluticasone combination therapy represents an evidence‐based, guideline‐recommended option for moderate‐to‐severe AR in ENT practice. Its dual mechanism, rapid onset, favourable safety profile and high patient acceptability support its integration into contemporary treatment algorithms, particularly for patients requiring enhanced symptom control beyond monotherapy. The combination represents a meaningful therapeutic advancement, and further research is needed to fully characterise its role in perennial AR management.